Extracorporeal Detoxification Methods and Hemostasis System for Ovarian Cancer Patients. Clinical Case - A. S. Safonov; M. V. Zabelin; A. A. Izmailov; Z. A. Valiullina; A. R. Mukhametkulova; A. V. Vasilchenko; K. N. Zolotukhin (Креативная хирургия и онкология)
Introduction. Malignant tumors dominate in the picture of disability and mortality worldwide. One of the most frequent and dangerous comorbid conditions is kidney injury. At the same time, the most unfavorable incidence of acute kidney injury is recorded in multiple myeloma, leukemia, lymphoma and kidney and/or liver cancer and malignant ovarian neoplasms. In this regard, of vital importance is the choice of tactics in the prevention of thrombosis and thromboembolic complications, as well as the individual approach to of the anticoagulant therapy regimen during renal replacement therapy sessions, depending on the underlying disease and the state of the hemostatic system.   Aim. To evaluate the effect of calcium citrate veno-venous hemodiafi ltration sessions on the hemostatic system of a patient with progressive organ dysfunctions associated with malignant ovarian neoplasm.   Materials and methods. The methodology involved literature review and a case study to assess the effect of veno-venous hemodiafi ltration on hemostasis.   Results and discussion. The clinical case was assessed in terms of P-selectin (CD62), which characterizes platelet activation processes. It should be noted that in this patient, the expression of P-selectin increased with each session of renal replacement therapy, while the platelet aggregation values remained at the level of the lower thresholds, which indicates a low probability of coagulation initiation. However, due to aggressive regulation of ovarian cancer by the hemostatic system in the form of production of inflammatory mediators, microvesicles, tissue factor expression and endothelial activation, attention should be paid to the molecular aspects of platelet activation in renal replacement therapy with regional citrate coagulation.   Conclusion. The widespread use of extracorporeal detoxification methods is an independent risk factor not only for bleeding events, but may potentially contribute to thrombosis and thromboembolic complications, which requires a further detailed study of molecular mechanisms of hemostasis regulation by tumor and clinical evaluation of various anticoagulation methods.